Development of Inflation Expectations in Serbia and a Comparative Analysis - Vesna Martin (Journal of Central Banking Theory and Practice, 2020)
Inflation expectations are very important when it comes to monetary policy and its decisions. In countries which are applying inflation targeting, inflation expectations reflect prediction of economic agents of movement of inflation rate in mid and long term. Anchored inflation expectations and their movements within target tolerance band are pointing to effectiveness of the inflation targeting strategy. Consistent with the best international practice, after introducing the inflation targeting regime in January 2009, the National Bank of Serbia began monitoring and analysing inflation expectations of economic agents (financial sector, corporate sector, trade unions, and households). The aim of this paper is to analyse inflation expectations in Serbia, but also to give a comparative analysis of inflation expectation of other countries which are using inflation targeting and floating exchange rate, as is the case of the National Bank of Serbia.
Keywords: E31; E52; E58; 330; inflation expectations; monetary policy; economic agents; anchored expectations.